Périplos norte-atlânticos da sociologia contemporânea: a sociologia pragmática - Michetti, Miqueli (Sociologias, 2019)
O texto apresenta o livro La sociologie pragmatique (A sociologia pragmática), em que Cyril Lemieux passa em revista os princípios, os conceitos e os métodos característicos dessa nova corrente disciplinar, além de discorrer sobre os principais “campos de pesquisa” trabalhados e sobre os debates centrais que a atravessam interna e externamente nas últimas décadas. A resenha busca ainda ancorar a obra e a vertente preconizada em seu contexto de emergência e publicização, atentando às disputas posicionais que a enformam. North Atlantic journeys of contemporary sociology: the pragmatic sociology Abstract The text presents a review of Cyril Lemieux’s La sociologie pragmatique (The pragmatic sociology), in which the author features the origins and affiliations of this new disciplinary branch and describes its central principles, concepts and methods. The French sociologist also introduces the main “fields of research” developed through the pragmatic approach in the last few decades, advancing its main internal and external debates. This review seeks to anchor both the book and the pragmatic sociology it advocates in their context of emergency and publicization, taking into account the positional disputes shaping them. Keywords: pragmatic sociology, sociology of action, post-Bourdieusian social theory.